Polyurethane composite material for outdoor environment container and preparation method thereof
By modifying the preparation of polyurethane on the outer and inner layer, combining nanosilica and nanosilver components, a cross-linking network structure is formed, which solves the problems of polyurethane materials being prone to yellowing, cracking and insufficient antibacterial properties in the wild environment, and improves wear resistance, anti-aging and antibacterial properties.
Patent Information
- Application Number
- CN202510774373.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2025-08-12
- Estimated Expiration
- 2045-06-11
AI Technical Summary
Existing polyurethane materials are prone to yellowing, cracking, deteriorating mechanical properties in the wild environment, and lack antibacterial properties.
By preparing modified outer polyurethane and modified inner polyurethane, combined with nanosilica, nanosilica, vitamin E and other components, a cross-linking network structure is formed to improve wear resistance, and antibacterial properties are improved through quaternary ammonium salts and phosphorus elements.
It has achieved the improvement of wear resistance, anti-aging and antibacterial properties of polyurethane materials in outdoor environments.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, in particular to a polyurethane composite material for outdoor environment containers and a preparation method thereof. Background Art
[0002] In the wild environment, the terrain is complex and the climate is changeable. Therefore, when selecting containers for the wild environment, they need to have characteristics such as wear resistance and flame retardancy. At the same time, the inner layer needs to have antibacterial properties. Polyurethane is widely used in various fields such as aerospace, weapons transportation and civil structural materials due to its excellent flame retardancy and wear resistance. However, when used in the wild environment, it is affected by environmental factors such as ultraviolet rays and heat in the environment, and is prone to yellowing, cracking, and degradation of mechanical properties. Therefore, the present invention designs a polyurethane composite material for wild environment containers with good wear resistance and aging resistance. Summary of the Invention
[0003] The object of the present invention is to provide a polyurethane composite material for outdoor environment containers and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0005] A polyurethane composite material for a field environment container, characterized in that the polyurethane composite material for a field environment container is obtained by hot pressing a modified outer layer polyurethane, a reinforcement layer, a polytetrafluoroethylene film, and a modified inner layer polyurethane;
[0006] The modified outer layer polyurethane is prepared by reacting pre-modified outer layer polyurethane with modified nano-silicon dioxide;
[0007] The pre-modified outer layer polyurethane is prepared by reacting 4,4-diisocyanate dicyclohexylmethane, hydroxyl-terminated vinylmethyl-dimethyl copolysiloxane, and polytetramethylene glycol to obtain an outer layer polyurethane prepolymer, which is then reacted with 1,4-butanediol.
[0008] The modified nano-silica is prepared by reacting nano-silica with ethylene (chloromethyl) dimethoxysilane to obtain pre-modified nano-silica, which is then reacted with 2,4-dihydroxybenzophenone to obtain the modified nano-silica.
[0009] The modified inner layer polyurethane is prepared by uniformly mixing the pre-modified inner layer polyurethane with a nano silver solution, vitamin E, and a hydrolysis stabilizer, and then ultrasonically dispersing the mixture.
[0010] The pre-modified inner layer polyurethane is prepared by reacting hexamethylene diisocyanate and polytetramethylene glycol to obtain an inner layer polyurethane prepolymer, which is then reacted with methyldiethanolamine and diethyl chloromethylphosphonate in sequence.
[0011] A method for preparing a polyurethane composite material for outdoor environment containers comprises the following preparation steps:
[0012] (1) Under nitrogen atmosphere, the outer layer polyurethane prepolymer and 1,4-butanediol were mixed evenly in a molar ratio of isocyanate group to hydroxyl group of 1: (1-1.02), stirred at 80-90 ° C and 200-300 r / min for 2-3 h, and N,N-dimethylformamide was removed by vacuum distillation. The pre-modified outer layer polyurethane was obtained by vacuum drying at 60-70 ° C for 8-10 h.
[0013] (2) The pre-modified outer layer polyurethane, modified nano-silica, azobisisobutyronitrile, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1: (0.2-0.4): (0.001-0.002): (15-20), stirred at 50-60°C and 200-300 r / min for 4-6 hours, poured into a mold, and vacuum dried at 35-45°C for 40-48 hours to obtain a modified outer layer polyurethane;
[0014] (3) Under nitrogen atmosphere, the inner layer polyurethane prepolymer and methyldiethanolamine were mixed evenly at a molar ratio of isocyanate group to hydroxyl group of 1: (1-1.02), stirred at 80-90 ° C, 200-300 r / min for 2-3 h, and 0.1-0.2 times the mass of the inner layer polyurethane prepolymer diethyl chloromethylphosphonate was added dropwise at a uniform rate within 20 min, stirred at 50-60 ° C, 200-300 r / min for 8-10 h, and cooled to room temperature to obtain a pre-modified inner layer polyurethane; the pre-modified inner layer polyurethane, nanosilver solution, vitamin E, and hydrolysis stabilizer were mixed evenly at a mass ratio of 1: (0.04-0.06): (0.002-0.004): (0.002-0.004), ultrasonically dispersed for 20-30 min, poured into a mold, and vacuum dried at 35-45 ° C for 40-48 h to obtain a modified inner layer polyurethane;
[0015] (4) The modified outer polyurethane layer, the reinforcement layer, the polytetrafluoroethylene film, and the modified inner polyurethane layer are stacked in sequence and hot pressed at 120-140°C and 8-12 MPa for 10-12 minutes to obtain a polyurethane composite material for field environment containers.
[0016] As an optimization, the preparation process of the outer layer polyurethane prepolymer in step (1) is as follows: under a nitrogen atmosphere, 4,4-diisocyanate dicyclohexylmethane, hydroxyl-terminated vinylmethyl-dimethyl copolysiloxane, and polytetrahydrofuran diol are uniformly mixed at a molar ratio of isocyanate group to hydroxyl group of 1: (0.6~0.7), and an organic bismuth compound with a mass of 0.004~0.006 times that of 4,4-diisocyanate dicyclohexylmethane and N,N-dimethylformamide with a mass of 15~20 times that of 4,4-diisocyanate dicyclohexylmethane are added, and the mixture is stirred at 80~90°C and 200~300r / min for 6~8h to obtain the outer layer polyurethane prepolymer.
[0017] As an optimization, the preparation process of the modified nano-silica in step (2) is as follows: pre-modified nano-silica, 2,4-dihydroxybenzophenone, triethylamine, and tetrahydrofuran are uniformly mixed in a mass ratio of 1: (0.8~1.2): (0.5~0.6): (15~20), stirred at 0~4°C and 200~300r / min for 4~6h, filtered and washed with saturated sodium bicarbonate aqueous solution 2~4 times, and vacuum dried at 50~60°C for 10~12h to obtain modified nano-silica.
[0018] As an optimization, the preparation process of the pre-modified nano-silica is as follows: ethylene (chloromethyl) dimethoxysilane and deionized water are evenly mixed in a mass ratio of 1: (1.8~2.2), nano-silica with a mass of 0.2~0.4 times that of ethylene (chloromethyl) dimethoxysilane and anhydrous ethanol with a mass of 5~7 times that of ethylene (chloromethyl) dimethoxysilane are added, the mixture is stirred at 70~80°C and 200~300r / min for 3~4h, the mixture is centrifuged at 8000~10000rpm for 10~12min, the resulting precipitate is washed 2~4 times with anhydrous ethanol, and vacuum dried at 60~70°C for 4~6h to obtain pre-modified nano-silica.
[0019] As an optimization, the preparation process of the inner layer polyurethane prepolymer in step (3) is as follows: under a nitrogen atmosphere, hexamethylene diisocyanate and polytetramethylene furan diol are uniformly mixed at a molar ratio of isocyanate group to hydroxyl group of 1: (0.6~0.7), and an organic bismuth compound with a mass of 0.004~0.006 times that of hexamethylene diisocyanate and N,N-dimethylformamide with a mass of 15~20 times that of hexamethylene diisocyanate are added, and the mixture is stirred at 80~90°C and 200~300r / min for 6~8h to obtain the inner layer polyurethane prepolymer.
[0020] As an optimization, the hydrolysis stabilizer in step (3) is: monomeric carbodiimide hydrolysis stabilizer Bio-SW100.
[0021] As an optimization, the reinforcement layer in step (4) is one of nylon, aramid, and high-strength polyester.
[0022] As an optimization, the model of the organic bismuth compound is BiCAT 8118.
[0023] As an optimization, the nano-silica was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0024] As an optimization, the hydroxyl-terminated vinylmethyl-dimethyl copolysiloxane has a weight average molecular weight of 550-650 and is purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0025] As an optimization, the weight-average molecular weight of the polytetrahydrofuran diol is 1000, which is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0026] As an optimization, the nanosilver solution has a nanosilver particle size of 4 nm and a silver element content of 2000 ppm, and is purchased from Hubei Xinrunde Chemical Co., Ltd.
[0027] As an optimization, the thickness of the polytetrafluoroethylene film is 0.2 mm and is purchased from Shenzhen Yizhong Technology Co., Ltd.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The invention prepares a polyurethane composite material for a field environment container by reacting nano-silica with ethylene (chloromethyl) dimethoxysilane to obtain pre-modified nano-silica, which is then reacted with 2,4-dihydroxybenzophenone to obtain modified nano-silica; 4,4-diisocyanate dicyclohexylmethane, hydroxyl-terminated vinylmethyl-dimethyl copolymerized siloxane, and polytetrahydrofuran diol are reacted to obtain an outer layer polyurethane prepolymer, which is then reacted with 1,4-butanediol to obtain a pre-modified outer layer polyurethane; the pre-modified outer layer polyurethane is reacted with the modified nano-silica. The method comprises the following steps: reacting with silica to obtain a modified outer polyurethane; reacting hexamethylene diisocyanate and polytetramethylene furan diol to obtain an inner polyurethane prepolymer; reacting the inner polyurethane prepolymer with methyldiethanolamine and then with diethyl chloromethylphosphonate to obtain a pre-modified inner polyurethane; adding nanosilver solution, vitamin E and a hydrolysis stabilizer for ultrasonic dispersion to obtain a modified inner polyurethane; and stacking the modified outer polyurethane, a reinforcement layer, a polytetrafluoroethylene film and the modified inner polyurethane in sequence and then hot pressing them to obtain a polyurethane composite material for field environment containers.
[0030] First, nano-silica is reacted with ethylene (chloromethyl) dimethoxysilane to obtain pre-modified nano-silica, which is then reacted with 2,4-dihydroxybenzophenone to obtain modified nano-silica. Nano-silica has good wear resistance. After reacting with ethylene (chloromethyl) dimethoxysilane, the compatibility of nano-silica with polyurethane materials is improved. At the same time, double bonds and halogenated hydrocarbons are introduced into nano-silica, which is then reacted with 2,4-dihydroxybenzophenone to introduce benzophenone-type UV absorbers into nano-silica, thereby improving the material. The anti-aging performance of the material is improved; 4,4-diisocyanate dicyclohexylmethane, hydroxyl-terminated vinylmethyl-dimethyl copolysiloxane, and polytetramethylene glycol are reacted to obtain an outer layer polyurethane prepolymer, which is then reacted with 1,4-butanediol to obtain a pre-modified outer layer polyurethane, and the pre-modified outer layer polyurethane is reacted with modified nano-silica to obtain a modified outer layer polyurethane, and modified nano-silica with good wear resistance is dispersed inside the polyurethane and reacts with double bonds on the polyurethane soft segment to form a cross-linked network structure, thereby further improving the wear resistance of the material.
[0031] Secondly, hexamethylene diisocyanate and polytetramethylene glycol are reacted to obtain an inner layer polyurethane prepolymer; the inner layer polyurethane prepolymer is reacted with methyldiethanolamine, and then with diethyl chloromethylphosphonate to obtain a pre-modified inner layer polyurethane; methyldiethanolamine is used as a chain extender, and a tertiary amine group is introduced into the hard segment of the inner layer polyurethane, and a quaternization reaction occurs with diethyl chloromethylphosphonate. The generated quaternary ammonium salt has good antibacterial properties, thereby improving the antibacterial properties of the material; at the same time, the addition of phosphorus element in diethyl chloromethylphosphonate improves the flame retardant properties of the material; the pre-modified inner layer polyurethane, nanosilver solution, vitamin E, and a hydrolysis stabilizer are mixed and ultrasonically dispersed to obtain a modified inner layer polyurethane; the nanosilver solution is used as an antibacterial agent, and synergistically fights bacteria with the quaternary ammonium salt, thereby further improving the antibacterial properties of the material. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0033] The reinforcing layer described in all the following examples and comparative examples is aramid plain woven fabric, model number Taparan® TH6301, purchased from Yantai Taihe New Materials Group Co., Ltd. Example 1
[0034] A method for preparing a polyurethane composite material for outdoor environment containers comprises the following preparation steps:
[0035] (1) Ethylene (chloromethyl) dimethoxysilane and deionized water were mixed in a mass ratio of 1:1.8, and nano-silica with a mass of 0.2 times that of ethylene (chloromethyl) dimethoxysilane and anhydrous ethanol with a mass of 5 times that of ethylene (chloromethyl) dimethoxysilane were added. The mixture was stirred at 70°C and 200 r / min for 3 h, and centrifuged at 8000 rpm for 10 min. The resulting precipitate was washed twice with anhydrous ethanol and vacuum dried at 60°C for 4 h to obtain pre-modified nano-silica.
[0036] (2) Pre-modified nano-silica, 2,4-dihydroxybenzophenone, triethylamine, and tetrahydrofuran were mixed uniformly in a mass ratio of 1:0.8:0.5:15, stirred at 0°C and 200 r / min for 4 h, filtered, washed twice with a saturated sodium bicarbonate aqueous solution, and vacuum dried at 50°C for 10 h to obtain modified nano-silica;
[0037] (3) Under nitrogen atmosphere, 4,4-diisocyanate dicyclohexylmethane, hydroxyl-terminated vinylmethyl-dimethyl copolysiloxane, and polytetramethylene glycol were mixed evenly at a molar ratio of isocyanate group to hydroxyl group of 1:0.6, and an organic bismuth compound with a mass of 0.004 times that of 4,4-diisocyanate dicyclohexylmethane and N,N-dimethylformamide with a mass of 15 times that of 4,4-diisocyanate dicyclohexylmethane were added, and the mixture was stirred at 80°C and 200 r / min for 6 hours to obtain an outer layer polyurethane prepolymer; Under nitrogen atmosphere, the outer layer polyurethane prepolymer and 1,4-butanediol were mixed evenly at a molar ratio of isocyanate group to hydroxyl group of 1:1, and the mixture was stirred at 80°C and 200 r / min for 2 hours, and N,N-dimethylformamide was removed by reduced pressure distillation, and the mixture was vacuum dried at 60°C for 8 hours to obtain a pre-modified outer layer polyurethane;
[0038] (4) The pre-modified outer layer polyurethane, modified nano-silica, azobisisobutyronitrile, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.2:0.001:15, stirred at 50°C and 200 r / min for 4 h, poured into a mold, and vacuum dried at 35°C for 40 h to obtain a modified outer layer polyurethane;
[0039] (5) Under nitrogen atmosphere, at a molar ratio of isocyanate group to hydroxyl group of 1:0.6, hexamethylene diisocyanate and polytetramethylene glycol were mixed evenly, and an organic bismuth compound of 0.004 times the mass of hexamethylene diisocyanate and N,N-dimethylformamide of 15 times the mass of hexamethylene diisocyanate were added, and stirred at 80°C and 200 r / min for 6 hours to obtain an inner layer polyurethane prepolymer; under nitrogen atmosphere, at a molar ratio of isocyanate group to hydroxyl group of 1:1, the inner layer polyurethane prepolymer and methyldiethanolamine were mixed evenly, The mixture was stirred at 80°C and 200 r / min for 2 hours, and diethyl chloromethylphosphonate (0.1 times the mass of the inner layer polyurethane prepolymer) was uniformly added dropwise within 20 minutes. The mixture was stirred at 50°C and 200 r / min for 8 hours, and cooled to room temperature to obtain a pre-modified inner layer polyurethane. The pre-modified inner layer polyurethane, nanosilver solution, vitamin E, and hydrolysis stabilizer were uniformly mixed in a mass ratio of 1:0.04:0.002:0.002, ultrasonically dispersed for 20 minutes, poured into a mold, and vacuum dried at 35°C for 40 hours to obtain a modified inner layer polyurethane.
[0040] (6) The modified outer polyurethane layer, the reinforcement layer, the polytetrafluoroethylene film, and the modified inner polyurethane layer were stacked in sequence and hot pressed at 120°C and 8 MPa for 10 minutes to obtain a polyurethane composite material for field environment containers. Example 2
[0041] A method for preparing a polyurethane composite material for outdoor environment containers comprises the following preparation steps:
[0042] (1) Ethylene (chloromethyl) dimethoxysilane and deionized water were mixed in a mass ratio of 1:2, and nano-silica with a mass of 0.3 times that of ethylene (chloromethyl) dimethoxysilane and anhydrous ethanol with a mass of 6 times that of ethylene (chloromethyl) dimethoxysilane were added. The mixture was stirred at 75°C and 250 r / min for 3.5 h, and centrifuged at 9000 rpm for 11 min. The resulting precipitate was washed three times with anhydrous ethanol and dried in vacuum at 65°C for 5 h to obtain pre-modified nano-silica.
[0043] (2) Pre-modified nano-silica, 2,4-dihydroxybenzophenone, triethylamine, and tetrahydrofuran were mixed uniformly in a mass ratio of 1:1:0.55:18, stirred at 2°C and 250 r / min for 5 h, filtered, washed three times with a saturated sodium bicarbonate aqueous solution, and vacuum dried at 55°C for 11 h to obtain modified nano-silica;
[0044] (3) Under nitrogen atmosphere, 4,4-diisocyanate dicyclohexylmethane, hydroxyl-terminated vinylmethyl-dimethyl copolysiloxane, and polytetramethylene glycol were mixed evenly at a molar ratio of isocyanate group to hydroxyl group of 1:0.65, and an organic bismuth compound with a mass of 0.005 times that of 4,4-diisocyanate dicyclohexylmethane and N,N-dimethylformamide with a mass of 18 times that of 4,4-diisocyanate dicyclohexylmethane were added. The mixture was stirred at 85°C and 250 r / min for 7 hours to obtain an outer layer polyurethane prepolymer; Under nitrogen atmosphere, the outer layer polyurethane prepolymer and 1,4-butanediol were mixed evenly at a molar ratio of isocyanate group to hydroxyl group of 1:1.01, and the mixture was stirred at 85°C and 250 r / min for 2.5 hours. N,N-dimethylformamide was removed by reduced pressure distillation, and the mixture was vacuum dried at 65°C for 9 hours to obtain a pre-modified outer layer polyurethane;
[0045] (4) The pre-modified outer layer polyurethane, modified nano-silica, azobisisobutyronitrile, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.3:0.0015:18, stirred at 55°C and 250 r / min for 5 h, poured into a mold, and vacuum dried at 40°C for 44 h to obtain a modified outer layer polyurethane;
[0046] (5) Under nitrogen atmosphere, at a molar ratio of isocyanate group to hydroxyl group of 1:0.65, hexamethylene diisocyanate and polytetramethylene glycol were mixed evenly, and an organic bismuth compound of 0.005 times the mass of hexamethylene diisocyanate and N,N-dimethylformamide of 18 times the mass of hexamethylene diisocyanate were added, and stirred at 85 ° C and 250 r / min for 7 hours to obtain an inner layer polyurethane prepolymer; under nitrogen atmosphere, at a molar ratio of isocyanate group to hydroxyl group of 1:1.01, the inner layer polyurethane prepolymer and methyldiethanolamine were mixed evenly. , stirring and reacting at 85°C and 250r / min for 2.5h, adding 0.15 times the mass of the inner layer polyurethane prepolymer of diethyl chloromethylphosphonate dropwise at a uniform speed within 20min, stirring and reacting at 55°C and 250r / min for 9h, cooling to room temperature to obtain a pre-modified inner layer polyurethane; the pre-modified inner layer polyurethane, nanosilver solution, vitamin E, and hydrolysis stabilizer are uniformly mixed in a mass ratio of 1:0.05:0.003:0.003, ultrasonically dispersed for 25min, poured into a mold, and vacuum dried at 40°C for 44h to obtain a modified inner layer polyurethane;
[0047] (6) The modified outer polyurethane layer, the reinforcement layer, the polytetrafluoroethylene film, and the modified inner polyurethane layer were stacked in sequence and hot pressed at 130°C and 10 MPa for 11 minutes to obtain a polyurethane composite material for field environment containers. Example 3
[0048] A method for preparing a polyurethane composite material for outdoor environment containers comprises the following preparation steps:
[0049] (1) Ethylene (chloromethyl) dimethoxysilane and deionized water were mixed in a mass ratio of 1:2.2, and nano-silica with a mass of 0.4 times that of ethylene (chloromethyl) dimethoxysilane and anhydrous ethanol with a mass of 7 times that of ethylene (chloromethyl) dimethoxysilane were added. The mixture was stirred at 80°C and 300 r / min for 4 h, and centrifuged at 10,000 rpm for 12 min. The resulting precipitate was washed 4 times with anhydrous ethanol and vacuum dried at 70°C for 6 h to obtain pre-modified nano-silica.
[0050] (2) Pre-modified nano-silica, 2,4-dihydroxybenzophenone, triethylamine, and tetrahydrofuran were mixed uniformly in a mass ratio of 1:1.2:0.6:20, stirred at 4°C and 300 r / min for 6 h, filtered, washed with saturated sodium bicarbonate aqueous solution 4 times, and vacuum dried at 60°C for 12 h to obtain modified nano-silica;
[0051] (3) Under nitrogen atmosphere, 4,4-diisocyanate dicyclohexylmethane, hydroxyl-terminated vinylmethyl-dimethyl copolysiloxane, and polytetramethylene glycol were mixed evenly at a molar ratio of isocyanate group to hydroxyl group of 1:0.7, and an organic bismuth compound with a mass of 0.006 times that of 4,4-diisocyanate dicyclohexylmethane and N,N-dimethylformamide with a mass of 20 times that of 4,4-diisocyanate dicyclohexylmethane were added, and the mixture was stirred at 90°C and 300 r / min for 8 hours to obtain an outer layer polyurethane prepolymer; Under nitrogen atmosphere, the outer layer polyurethane prepolymer and 1,4-butanediol were mixed evenly at a molar ratio of isocyanate group to hydroxyl group of 1:1.02, and the mixture was stirred at 90°C and 300 r / min for 3 hours, and N,N-dimethylformamide was removed by reduced pressure distillation, and the mixture was vacuum dried at 70°C for 10 hours to obtain a pre-modified outer layer polyurethane;
[0052] (4) The pre-modified outer layer polyurethane, modified nano-silica, azobisisobutyronitrile, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.4:0.002:20, stirred at 60°C and 300 r / min for 6 h, poured into a mold, and vacuum dried at 45°C for 48 h to obtain a modified outer layer polyurethane;
[0053] (5) Under nitrogen atmosphere, at a molar ratio of isocyanate group to hydroxyl group of 1:0.7, hexamethylene diisocyanate and polytetramethylene glycol were mixed evenly, and an organic bismuth compound of 0.006 times the mass of hexamethylene diisocyanate and N,N-dimethylformamide of 20 times the mass of hexamethylene diisocyanate were added, and stirred at 90 ° C and 300 r / min for 8 hours to obtain an inner layer polyurethane prepolymer; under nitrogen atmosphere, at a molar ratio of isocyanate group to hydroxyl group of 1:1.02, the inner layer polyurethane prepolymer and methyldiethanolamine were mixed evenly. , stirring and reacting at 90°C and 300r / min for 3h, adding 0.2 times the mass of the inner layer polyurethane prepolymer of diethyl chloromethylphosphonate dropwise at a uniform speed within 20min, stirring and reacting at 60°C and 300r / min for 10h, cooling to room temperature to obtain a pre-modified inner layer polyurethane; the pre-modified inner layer polyurethane, nanosilver solution, vitamin E, and hydrolysis stabilizer are uniformly mixed in a mass ratio of 1:0.06:0.004:0.004, ultrasonically dispersed for 30min, poured into a mold, and vacuum dried at 45°C for 48h to obtain a modified inner layer polyurethane;
[0054] (6) The modified outer polyurethane layer, the reinforcement layer, the polytetrafluoroethylene film, and the modified inner polyurethane layer were stacked in sequence and hot pressed at 140°C and 12 MPa for 12 minutes to obtain a polyurethane composite material for field environment containers.
[0055] Comparative Example 1:
[0056] The method for preparing a polyurethane composite material for a field environment container in Comparative Example 1 differs from that in Example 2 in that steps (1) and (2) are omitted, and step (4) is modified as follows: pre-modified outer layer polyurethane, nano-silica, azobisisobutyronitrile, and N,N-dimethylformamide are uniformly mixed in a mass ratio of 1:0.3:0.0015:18, stirred at 55°C and 250 r / min for 5 h, poured into a mold, and vacuum dried at 40°C for 44 h to obtain a modified outer layer polyurethane. The remaining steps are the same as in Example 2.
[0057] Comparative Example 2:
[0058] The method for preparing a polyurethane composite material for a field environment container in Comparative Example 2 differs from that in Example 2 in that steps (1) and (2) are omitted, and step (4) is modified as follows: the pre-modified outer layer polyurethane and N,N-dimethylformamide are uniformly mixed in a mass ratio of 1:20, stirred at 60°C and 300 rpm for 6 hours, poured into a mold, and vacuum-dried at 45°C for 48 hours to obtain a modified outer layer polyurethane. The remaining steps are the same as in Example 2.
[0059] Comparative Example 3:
[0060] The preparation method of the polyurethane composite material for field environment container of comparative example 3 is different from that of example 2 in step (5). Step (5) is modified as follows: under nitrogen atmosphere, according to the molar ratio of isocyanate group to hydroxyl group of 1:0.65, hexamethylene diisocyanate and polytetrahydrofuran diol are uniformly mixed, and an organic bismuth compound with a mass of 0.005 times that of hexamethylene diisocyanate and N,N-dimethylformamide with a mass of 18 times that of hexamethylene diisocyanate are added, and the reaction is stirred at 85°C and 250r / min for 7h to obtain the inner layer polyurethane composite material. Ester prepolymer; under a nitrogen atmosphere, the inner layer polyurethane prepolymer and methyldiethanolamine were uniformly mixed at a molar ratio of isocyanate group to hydroxyl group of 1:1.01, stirred at 85°C and 250 rpm for 2.5 hours, and cooled to room temperature to prepare a pre-modified inner layer polyurethane; the pre-modified inner layer polyurethane, nanosilver solution, vitamin E, and hydrolysis stabilizer were uniformly mixed at a mass ratio of 1:0.05:0.003:0.003, ultrasonically dispersed for 25 minutes, poured into a mold, and vacuum dried at 40°C for 44 hours to prepare a modified inner layer polyurethane. The remaining steps were the same as in Example 2.
[0061] Comparative Example 4:
[0062] The preparation method of the polyurethane composite material for outdoor environment in Comparative Example 4 is different from that in Example 2 in step (5). Step (5) is modified as follows: under a nitrogen atmosphere, according to the molar ratio of isocyanate group to hydroxyl group of 1:0.65, hexamethylene diisocyanate and polytetrahydrofuran diol are uniformly mixed, and an organic bismuth compound with a mass of 0.005 times that of hexamethylene diisocyanate and N,N-dimethylformamide with a mass of 18 times that of hexamethylene diisocyanate are added, and the mixture is stirred at 85°C and 250r / min for 7h to obtain an inner layer polyurethane prepolymer; under a nitrogen atmosphere, according to the molar ratio of isocyanate group to hydroxyl group of 1:0.65, an organic bismuth compound with a mass of 0.005 times that of hexamethylene diisocyanate and N,N-dimethylformamide with a mass of 18 times that of hexamethylene diisocyanate are added, and the mixture is stirred at 85°C and 250r / min for 7h to obtain an inner layer polyurethane prepolymer; The inner layer polyurethane prepolymer and methyldiethanolamine were uniformly mixed in a mass ratio of 1:1.01, stirred and reacted at 85°C and 250 r / min for 2.5 hours, and diethyl chloromethylphosphonate (0.15 times the mass of the inner layer polyurethane prepolymer) was uniformly added dropwise over 20 minutes. The mixture was stirred and reacted at 55°C and 250 r / min for 9 hours, and cooled to room temperature to obtain a pre-modified inner layer polyurethane. The pre-modified inner layer polyurethane, vitamin E, and a hydrolysis stabilizer were uniformly mixed in a mass ratio of 1:0.003:0.003, ultrasonically dispersed for 25 minutes, poured into a mold, and vacuum dried at 40°C for 44 hours to obtain a modified inner layer polyurethane. The remaining steps were the same as in Example 2.
[0063] Test Example 1:
[0064] Wear resistance test:
[0065] The polyurethane composite materials for field environment containers obtained in each embodiment and comparative example were made into test specimens of uniform size and 3.2 mm thickness according to GB / T1689-2014. The modified inner polyurethane surface of the test specimen was adhered to a rubber wheel and rubbed against the modified outer polyurethane surface to test the wear volume of the polyurethane material.
[0066] The results are shown in Table 1:
[0067] Table 1
[0068]
[0069] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the polyurethane composite material for outdoor environment containers prepared in the present invention has good wear resistance.
[0070] By comparison, the wear volume of Examples 1 to 3 is greater than the wear volume of Comparative Examples 1 to 2, indicating that the nano-silica has good wear resistance. After reacting with ethylene (chloromethyl) dimethoxysilane, the compatibility of the nano-silica and the polyurethane material is improved. At the same time, double bonds are introduced into the nano-silica, which react with the double bonds of the pre-modified outer polyurethane soft segment to form a cross-linked network structure, thereby improving the wear resistance of the polyurethane composite material for outdoor environment containers.
[0071] Test Example 2:
[0072] Anti-aging performance test:
[0073] The polyurethane composite materials for outdoor environment containers obtained in each embodiment and comparative example were respectively made into test specimens of 10 cm×10 mm×1 mm, and tested with reference to GB / T1040.2-2022 at a tensile speed of 10 mm / min to test the tensile strength M.
[0074] The polyurethane composite materials for outdoor environment containers obtained in each embodiment and the comparative example were made into test samples of 10 cm×10 mm×1 mm, and subjected to fluorescent ultraviolet light exposure test according to GB / T16422.3-2022, that is, the irradiance of 340 nm light was 0.76 W / (m 2 ·nm), the blackboard temperature is 60℃, the exposure cycle is dried for 8h and condensed for 4h; the tensile strength N is tested again, and the performance degradation rate is calculated as 1-N / M×100%.
[0075] The results are shown in Table 2.
[0076] Table 2
[0077]
[0078] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the polyurethane composite material for outdoor environment containers prepared in the present invention has good anti-aging performance.
[0079] By comparison, the performance degradation rates of Examples 1 to 3 are less than the performance degradation rates of Comparative Examples 1 to 2, indicating that pre-modified nano-silica is prepared by reacting nano-silica with ethylene (chloromethyl) dimethoxysilane, which is then reacted with 2,4-dihydroxybenzophenone to prepare modified nano-silica. After the nano-silica reacts with ethylene (chloromethyl) dimethoxysilane, double bonds and halogenated hydrocarbons are introduced into the nano-silica, which is then reacted with 2,4-dihydroxybenzophenone to introduce a benzophenone-type ultraviolet absorber into the silica, thereby improving the anti-aging performance of the polyurethane composite material for outdoor environment containers.
[0080] Test Example 3:
[0081] Flame retardant performance test:
[0082] The polyurethane composite materials for field environment containers obtained in the examples and comparative examples were made into standard specimens according to GB / T2406.2-2009, and the limiting oxygen index was tested.
[0083] The results are shown in Table 3.
[0084] Table 3
[0085]
[0086] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the polyurethane composite material for outdoor environment containers prepared in the present invention has good flame retardant properties.
[0087] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 3, indicating that the inner layer polyurethane prepolymer reacts with methyldiethanolamine and then with diethyl chloromethylphosphonate to prepare a pre-modified inner layer polyurethane, and phosphorus is introduced into the inner layer polyurethane, thereby improving the flame retardant properties of the polyurethane composite material for outdoor environment containers.
[0088] Test Example 4:
[0089] Antibacterial test: The specific test methods are as follows:
[0090] The polyurethane composite coatings for field containers obtained in each embodiment and comparative example were used to make 50 mm × 50 mm test specimens and sterilized with an ultraviolet sterilization lamp for 5 minutes. Referring to GB / T 21866-2008 "Determination of Antibacterial Properties and Antibacterial Effects of Antimicrobial Coatings (Paint Films)", bacterial liquid was added dropwise to the modified inner polyurethane surface of the test specimens, and the antibacterial rates against Escherichia coli and Staphylococcus aureus were calculated.
[0091] The results are shown in Table 4.
[0092] Table 4
[0093]
[0094] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 4, it can be found that the polyurethane composite material for outdoor environment containers prepared in the present invention has good antibacterial properties.
[0095] By comparison, the antibacterial properties of Examples 1 to 3 are greater than the antibacterial rate of Comparative Example 3, indicating that methyldiethanolamine is used as a chain extender to introduce a tertiary amine group into the hard segment of the inner polyurethane layer, and a quaternization reaction occurs with diethyl chloromethylphosphonate. The generated quaternary ammonium salt has good antibacterial properties, thereby improving the antibacterial properties of the polyurethane composite material for outdoor environment containers.
[0096] By comparison, the antibacterial properties of Examples 1 to 3 are greater than the antibacterial rate of Comparative Example 4, indicating that the pre-modified inner polyurethane and the nanosilver solution are evenly mixed and ultrasonically dispersed to obtain the modified inner polyurethane. The nanosilver solution, as a common antibacterial agent, is dispersed in the pre-modified polyurethane and synergistically acts with the generated quaternary ammonium salt to further improve the antibacterial properties of the polyurethane composite material for outdoor containers.
[0097] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a polyurethane composite material for outdoor environment containers, characterized in that: The method comprises the following preparation steps: (1) Under nitrogen atmosphere, the outer layer polyurethane prepolymer and 1,4-butanediol were mixed evenly in a molar ratio of isocyanate group to hydroxyl group of 1: (1-1.02), stirred at 80-90 ° C and 200-300 r / min for 2-3 h, and N,N-dimethylformamide was removed by vacuum distillation. The pre-modified outer layer polyurethane was obtained by vacuum drying at 60-70 ° C for 8-10 h. (2) The pre-modified outer layer polyurethane, modified nano-silica, azobisisobutyronitrile, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1: (0.2-0.4): (0.001-0.002): (15-20), stirred at 50-60°C and 200-300 r / min for 4-6 hours, poured into a mold, and vacuum dried at 35-45°C for 40-48 hours to obtain a modified outer layer polyurethane; (3) Under nitrogen atmosphere, the inner layer polyurethane prepolymer and methyldiethanolamine were mixed evenly at a molar ratio of isocyanate group to hydroxyl group of 1: (1-1.02), stirred at 80-90 ° C, 200-300 r / min for 2-3 h, and 0.1-0.2 times the mass of the inner layer polyurethane prepolymer diethyl chloromethylphosphonate was added dropwise at a uniform rate within 20 min, stirred at 50-60 ° C, 200-300 r / min for 8-10 h, and cooled to room temperature to obtain a pre-modified inner layer polyurethane; the pre-modified inner layer polyurethane, nanosilver solution, vitamin E, and hydrolysis stabilizer were mixed evenly at a mass ratio of 1: (0.04-0.06): (0.002-0.004): (0.002-0.004), ultrasonically dispersed for 20-30 min, poured into a mold, and vacuum dried at 35-45 ° C for 40-48 h to obtain a modified inner layer polyurethane; (4) The modified outer polyurethane layer, the reinforcement layer, the polytetrafluoroethylene film, and the modified inner polyurethane layer are stacked in sequence, and hot pressed at 120-140°C and 8-12 MPa for 10-12 minutes to obtain a polyurethane composite material for field environment containers; The preparation process of the outer layer polyurethane prepolymer in step (1) is as follows: under a nitrogen atmosphere, 4,4-diisocyanate dicyclohexylmethane, hydroxyl-terminated vinylmethyl-dimethyl copolysiloxane, and polytetrahydrofuran diol are uniformly mixed at a molar ratio of isocyanate group to hydroxyl group of 1: (0.6-0.7), an organic bismuth compound of 0.004-0.006 times the mass of 4,4-diisocyanate dicyclohexylmethane and N,N-dimethylformamide of 15-20 times the mass of 4,4-diisocyanate dicyclohexylmethane are added, and the mixture is stirred at 80-90° C. and 200-300 r / min for 6-8 hours to obtain the outer layer polyurethane prepolymer; The preparation process of the modified nano-silica in step (2) is as follows: pre-modified nano-silica, 2,4-dihydroxybenzophenone, triethylamine, and tetrahydrofuran are uniformly mixed in a mass ratio of 1: (0.8-1.2): (0.5-0.6): (15-20), stirred at 0-4°C and 200-300 r / min for 4-6 hours, filtered, washed with a saturated sodium bicarbonate aqueous solution 2-4 times, and vacuum dried at 50-60°C for 10-12 hours to obtain modified nano-silica; The preparation process of the inner layer polyurethane prepolymer in step (3) is as follows: under a nitrogen atmosphere, hexamethylene diisocyanate and polytetramethylene furan diol are uniformly mixed at a molar ratio of isocyanate group to hydroxyl group of 1: (0.6~0.7), an organic bismuth compound of 0.004~0.006 times the mass of hexamethylene diisocyanate and N,N-dimethylformamide of 15~20 times the mass of hexamethylene diisocyanate are added, and the mixture is stirred at 80~90°C and 200~300r / min for 6~8h to obtain the inner layer polyurethane prepolymer.
2. The method for preparing a polyurethane composite material for outdoor environment containers according to claim 1, characterized in that: The hydrolysis stabilizer in step (3) is: monomeric carbodiimide hydrolysis stabilizer Bio-SW100.
3. The method for preparing a polyurethane composite material for outdoor environment containers according to claim 1, characterized in that: The reinforcing layer in step (4) is one of nylon, aramid, and high-strength polyester.
4. The method for preparing a polyurethane composite material for outdoor environment containers according to claim 1, characterized in that: The preparation process of the pre-modified nano-silica comprises the following steps: uniformly mixing ethylene (chloromethyl) dimethoxysilane and deionized water in a mass ratio of 1: (1.8-2.2), adding nano-silica in an amount 0.2-0.4 times the mass of ethylene (chloromethyl) dimethoxysilane and anhydrous ethanol in an amount 5-7 times the mass of ethylene (chloromethyl) dimethoxysilane, stirring at 70-80°C and 200-300 r / min for reaction for 3-4 hours, centrifuging at 8000-10000 rpm for 10-12 minutes, washing the resulting precipitate with anhydrous ethanol 2-4 times, and vacuum drying at 60-70°C for 4-6 hours to obtain the pre-modified nano-silica.
5. The method for preparing a polyurethane composite material for outdoor environment containers according to claim 1, characterized in that: The model of the organic bismuth compound is BiCAT 8118. 6 . A polyurethane composite material for field environment containers prepared according to the method for preparing a polyurethane composite material for field environment containers according to any one of claims 1 to 5 .
Citation Information
Patent Citations
Anti-aging double-wall fluoropolymer heat-shrinkable tubing and preparation method thereof
CN115091818A
Wear-resistant impact-resistant polyurethane material and preparation method thereof
CN118685024A